Corporate Governance: A Cybernetic View - Kummamuru, Venugopal (IUP Journal of Corporate Governance, 2016)
The word corporate governance is liberally used by many in the industry and has become a subject of intense discussion all over the world. Different definitions have been provided by various individuals/groups, which have given rise to questions like what is corporate governance? Its need, expectations and who is responsible for it? While discussing corporate governance, the focus remains mainly on the board of directors and financial aspects giving an impression that corporate governance is related only to these aspects though it is not so. In any organization, there are different entities. It is essential to understand the relationships and influences among different entities of an organization to understand the function of corporate governance. This paper attempts to provide a comprehensive definition of corporate governance after taking a cybernetic view of the function and applying the concepts of the Viable Systems Model developed by Stafford Beer. A cybernetic view of corporate governance while bringing in clarity also leads to a more complete and viable definition of corporate governance, fulfilling the purpose of this paper.